SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Environmental identities of college students reveal potential conflicts and common ground for wildlife conservation - Richard Von Furstenberg; Lincoln R. Larson; M. Nils Peterson; Kangjae Jerry Lee; Victoria R. Vayer; kathryn stevenson; Stacy A.C. Nelson; Jeremy Bruskotter; Adam A. Ahlers; Christine Anhalt-Depies; Taniya Bethke; Chris Chizinski; et al. (Biological Conservation, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Acquisition of elemental sulfur by sulfur‐oxidising Sulfolobales - Maria C. Fernandes‐Martins; Carli Springer; Daniel R. Colman; Eric S. Boyd (Environmental Microbiology, 2024)
Elemental sulfur (S 8 0 )‐oxidising Sulfolobales (Archaea) dominate high‐temperature acidic hot springs (>80°C, pH 8 0 ‐oxidising members of the Sulfolobales reveal a patchy distribution of genes encoding sulfur oxygenase reductase (SOR), an S 8 0 disproportionating enzyme attributed to S 8 0 oxidation. Here, we report the S 8 0 ‐dependent growth of two Sulfolobales strains previously isolated from acidic hot springs in Yellowstone National Park, one of which associated with bulk S 8 0 during growth and one that did not. The genomes of each strain encoded different sulfur metabolism enzymes, with only one encoding SOR. Dialysis membrane experiments showed that direct contact is not required for S 8 0 oxidation in the SOR‐encoding strain. This is attributed to the generation of hydrogen sulfide (H 2 S) from S 8 0 disproportionation that can diffuse out of the cell to solubilise bulk S 8 0 to form soluble polysulfides (S x 2− ) and/or S 8 0 nanoparticles that readily diffuse across dialysis membranes. The Sulfolobales strain lacking SOR required direct contact to oxidise S 8 0 , which could be overcome by the addition of H 2 S. High concentrations of S 8 0 inhibited the growth of both strains. These results implicate alternative strategies to acquire and metabolise sulfur in Sulfolobales and have implications for their distribution and ecology in their hot spring habitats.

Landscape context and behavioral clustering contribute to flexible habitat selection strategies in a large mammal - Nathan D. Hooven; Kathleen E. Williams; John T. Hast; Joseph R. McDermott; R. Daniel Crank; Matthew T. Springer; John J. Cox (Mammal Research, 2024)

Correlates of mid-winter pregnancy and early reproductive outcomes in a reintroduced elk (Cervus canadensis) population - Nathan D. Hooven; Kathleen E. Williams; John T. Hast; Joseph R. McDermott; R. Daniel Crank; Matthew T. Springer; John J. Cox (Mammalian Biology, 2024)

Cryopreservation of Anopheles stephensi (MOSQUITO) EGGS: EFFECTS ON GENOTYPIC AND PHENOTYPIC CHARACTERISTICS - Morgan Douglas; Ehud Inbar; Igor Sharakov; Najib M. El-Sayed; Ashton T. Belew; James Overby; Steve Matheny; Fantahun Addisu; Yonas Abebe; Dimitri Koutzoumis; Kerri Springer; Abraham Eappen; et al. (Cryobiology, 2023)

Confounding effects of snow cover on remotely sensed vegetation indices of evergreen and deciduous trees: An experimental study - Ran Wang; Kyle R. Springer; John A. Gamon (Global Change Biology, 2023)
Located at northern latitudes and subject to large seasonal temperature fluctuations, boreal forests are sensitive to the changing climate, with evidence for both increasing and decreasing productivity, depending upon conditions. Optical remote sensing of vegetation indices based on spectral reflectance offers a means of monitoring vegetation photosynthetic activity and provides a powerful tool for observing how boreal forests respond to changing environmental conditions. Reflectance‐based remotely sensed optical signals at northern latitude or high‐altitude regions are readily confounded by snow coverage, hampering applications of satellite‐based vegetation indices in tracking vegetation productivity at large scales. Unraveling the effects of snow can be challenging from satellite data, particularly when validation data are lacking. In this study, we established an experimental system in Alberta, Canada including six boreal tree species, both evergreen and deciduous, to evaluate the confounding effects of snow on three vegetation indices: the normalized difference vegetation index (NDVI), the photochemical reflectance index (PRI), and the chlorophyll/carotenoid index (CCI), all used in tracking vegetation productivity for boreal forests. Our results revealed substantial impacts of snow on canopy reflectance and vegetation indices, expressed as increased albedo, decreased NDVI values and increased PRI and CCI values. These effects varied among species and functional groups (evergreen and deciduous) and different vegetation indices were affected differently, indicating contradictory, confounding effects of snow on these indices. In addition to snow effects, we evaluated the contribution of deciduous trees to vegetation indices in mixed stands of evergreen and deciduous species, which contribute to the observed relationship between greenness‐based indices and ecosystem productivity of many evergreen‐dominated forests that contain a deciduous component. Our results demonstrate confounding and interacting effects of snow and vegetation type on vegetation indices and illustrate the importance of explicitly considering snow effects in any global‐scale photosynthesis monitoring efforts using remotely sensed vegetation indices.

183 Effects of prolonged hay net feeding on equine behavior - M.R. Locke; T.D. Cross; A. Hoglan; R. Springer; K.A. Guay; K. Wellmann; R. Martínez; T.N. Jones (Journal of Equine Veterinary Science, 2023)

Anatomical, Ontogenetic, and Genomic Homologies Guide Reconstructions of the Teeth-to-Baleen Transition in Mysticete Whales - John Gatesy; Eric G. Ekdale; Thomas A. Deméré; Agnese Lanzetti; Jason Randall; Annalisa Berta; Joseph J. El Adli; Mark S. Springer; Michael R. McGowen (Journal of Mammalian Evolution, 2022)

Jamaican bioethanol: an environmental and economic life cycle assessment - E. Batuecas; R. Contreras-Lisperguer; C. Mayo; R. Díaz; C. Springer; F. J. Pérez (Clean Technologies and Environmental Policy, 2021)

Stakeholder Perceptions of White Oak Supply in Kentucky: A SWOT-AHP Analysis - William R. Thomas; Thomas O. Ochuodho; Chad F. Niman; Matthew T. Springer; Domena A. Agyeman; Laura R. Lhotka (Small-scale Forestry, 2021)

10th Anniversary of the European Association for Predictive, Preventive and Personalised (3P) Medicine - EPMA World Congress Supplement 2020 - Olga Golubnitschaja; Ondrej Topolcan; Radek Kucera; Vincenzo Costigliola; M. Akopyan; S. N. Akulov; O Alexandrova; Angel Alonso; Russell J. Andrews; A Assuane Duarte; O. Azarova; Maximilian Babel; et al. (EPMA Journal, 2020)
In 2019, the EPMA celebrated its 10th anniversary at the 5th World Congress in Pilsen, Czech Republic. The history of the International Professional Network dedicated to Predictive, Preventive and Personalised Medicine (PPPM / 3PM) is rich in achievements. Facing the coronavirus COVID-19 pandemic it is getting evident globally that the predictive approach, targeted prevention and personalisation of medical services is the optimal paradigm in healthcare demonstrating the high potential to save lives and to benefit the society as a whole. The EPMA World Congress Supplement 2020 highlights advances in 3P medicine.

Correction to: Review of GPS collar deployments and performance on nonhuman primates - Kerry M. Dore; Malene F. Hansen; Amy R. Klegarth; Claudia Fichtel; Flávia Koch; Andrea Springer; Peter Kappeler; Joyce A. Parga; Tatyana Humle; Christelle Colin; Estelle Raballand; Zhi-Pang Huang; et al. (Primates, 2020)

Review of GPS collar deployments and performance on nonhuman primates - Kerry M. Dore; Malene F. Hansen; Amy R. Klegarth; Claudia Fichtel; Flávia Koch; Andrea Springer; Peter Kappeler; Joyce A. Parga; Tatyana Humle; Christelle Colin; Estelle Raballand; Zhi-Pang Huang; et al. (Primates, 2020)

Utilization of deletion bins to anchor and order sequences along the wheat 7B chromosome - Tatiana Belova; Lars Grønvold; Ajay Kumar; Shahryar Kianian; Xinyao He; Morten Lillemo; Nathan M. Springer; Sigbjørn Lien; Odd-Arne Olsen; Simen R. Sandve (Theoretical and Applied Genetics, 2014)

An institutional strategy to increase minority recruitment to therapeutic trials - Victoria V. Anwuri; Lannis E. Hall; Katherine Mathews; Brian C. Springer; Jennifer R. Tappenden; Dione M. Farria; Sherrill Jackson; Melody S. Goodman; Timothy J. Eberlein; Graham A. Colditz (Cancer Causes & Control, 2013)

Contrasting effects of sunitinib within in vivo models of metastasis - Jonathan C. Welti; Thomas Powles; Shane Foo; Morgane Gourlaouen; Natasha Preece; Julie Foster; Sophia Frentzas; Demelza Bird; Kevin Sharpe; Antoinette van Weverwijk; David Robertson; Julie Soffe; et al. (Angiogenesis, 2012)

Comprehensive trend analysis of nutrients and related variables in a large eutrophic estuary: A decadal study of anthropogenic and climatic influences - JoAnn M. Burkholder; David A. Dickey; Carol A. Kinder; Robert E. Reed; Michael A. Mallin; Matthew R. McIver; Lawrence B. Cahoon; Greg Melia; Cavell Brownie; Joy Smith; Nora Deamer; Jeffrey Springer; et al. (Limnology and Oceanography, 2006)
We used a decadal data set, with weekly to biweekly sampling in April—October and monthly sampling in November—March, to characterize climatic (hurricane‐level storms, a sustained 3‐yr drought) and anthropogenic influences on N and P concentrations and loadings to a large eutrophic, poorly flushed estuary, the Neuse Estuary of the Albemarle—Pamlico Estuarine System. Mass volume transport data were obtained with cross‐estuary transect flow measurements taken near the entrance to the estuary. Although trends were minimally influenced by hurricanes, analyses were significantly affected by the sustained drought near the end of the study. As examples, decreasing trends in total N (TN), total P (TP), and bottom‐water dissolved oxygen concentrations, and in TN loadings were significant considering all data, but these trends were not significant when the sustained drought was excluded from analysis. In addition, the trend in TN loading was especially sensitive to the initial sampling period. NH 4 + concentrations dramatically increased (overall by ~500%) as a persistent trend regardless of attempts to control for climatic events. An increasing trend in NH 4 + also was documented in an adjacent, rapidly flushed Coastal Plain estuary, the Cape Fear. The NH 4 + data suggest a regional‐scale effect of high inputs from inadequately controlled, increasing nonpoint sources. The fragility of TN loading trends, the striking increase in NH 4 + concentrations, and the lack of management emphasis on controlling nonpoint sources such as “new” industrialized swine production collectively do not support recent reports of achievement of a 30% reduction in TN loading to the Neuse. Nonpoint sources remain a critical target for reduction to alleviate the negative effects of cultural eutrophication in this system, as in many estuaries throughout the world.

Case Study Part 2: Probabilistic Modelling of Long-term Effects of Pesticides on Individual Breeding Success in Birds and Mammals - W. ROELOFS; D.R. CROCKER; R.F. SHORE; D.R.J. MOORE; G.C. SMITH; H.R. AKCAKAYA; R.S. BENNETT; P.F. CHAPMAN; M. CLOOK; M. CRANE; I.C. DEWHURST; P.J. EDWARDS; et al. (Ecotoxicology, 2005)

Case Study Part 1: How to Calculate Appropriate Deterministic Long-Term Toxicity to Exposure Ratios (TERs) for Birds and Mammals - R.F. SHORE; D.R. CROCKER; H.R. AKCAKAYA; R.S. BENNETT; P.F. CHAPMAN; M. CLOOK; M. CRANE; I.C. DEWHURST; P.J. EDWARDS; A. FAIRBROTHER; S. FERSON; D. FISCHER; et al. (Ecotoxicology, 2005)

Relationships Among Families of Diprotodontia (Marsupialia) and the Phylogenetic Position of the Autapomorphic Honey Possum (Tarsipes rostratus) - John R. Kavanagh; Angela Burk-Herrick; Mike Westerman; Mark S. Springer (Journal of Mammalian Evolution, 2004)

Heterologous expression of a keto hexokinase in potato plants leads to inhibited rates of photosynthesis, severe growth retardation and abnormal leaf development - Peter Geigenberger; Babette Regierer; Anna Lytovchenko; Andrea Leisse; Nicolas Schauer; Fransiska Springer; Jens Kossmann; Alisdair R. Fernie (Planta, 2004)

Immunohistochemical Localization of Cardio-Active Neuropeptides in the Heart of a Living Fossil, Nautilus pompilius L. (Cephalopoda, Tetrabranchiata) - J. Springer; P. Ruth; K. Beuerlein; B. Westermann; R. Schipp (Journal of Molecular Histology, 2004)

Time transfer using GPS carrier phase: error propagation and results - R. Dach; G. Beutler; U. Hugentobler; S. Schaer; T. Schildknecht; T. Springer; G. Dudle; L. Prost (Journal of Geodesy, 2003)

The Arabidopsis gene PROLIFERA is required for proper cytokinesis during seed development - David R. Holding; Patricia S. Springer (Planta, 2002)

The international GLONASS experiment: products, progress and prospects - R. Weber; T. A. Springer (Journal of Geodesy, 2001)

Analysis of the first year of Earth rotation parameters with a sub-daily resolution gained at the CODE processing center of the IGS - J. Hefty; M. Rothacher; T. Springer; R. Weber; G. Beutler (Journal of Geodesy, 2000)

An Analysis of Marsupial Interordinal Relationships Based on 12S rRNA, tRNA Valine, 16S rRNA, and Cytochrome b Sequences - Angela Burk; Michael Westerman; Diana J. Kao; John R. Kavanagh; Mark S. Springer (Journal of Mammalian Evolution, 1999)

The influence of alterations in ADP-glucose pyrophosphorylase activities on starch structure and composition in potato tubers - James R. Lloyd; Franziska Springer; Alain Buléon; Bernd Müller-Röber; Lothar Willmitzer; Jens Kossmann (Planta, 1999)

Cloning and functional analysis of a cDNA encoding a starch synthase from potato ( Solanum tuberosum L.) that is predominantly expressed in leaf tissue - Jens Kossmann; Gernot J. W. Abel; Franziska Springer; James R. Lloyd; Lothar Willmitzer (Planta, 1999)

Sex-limited genetic variation in a mouse salivary protein - Robert C. Karn; Stephen R. Dlouhy; Kenneth R. Springer; J. Peter Hjorth; J. Tnnes Nielsen (Biochemical Genetics, 1982)

Aryl hydrocarbon hydroxylase activity in pulmonary alveolar macrophages and lymphocytes from lung cancer and noncancer patients: A correlation with family histories of cancer - T. L. McLemore; R. R. Martin; R. R. Springer; N. Wray; E. T. Cantrell; D. L. Busbee (Biochemical Genetics, 1979)